Analysis of Palm Fiber and Coconut Coir Usage as Purse Seine Cargo Chamber Insulator - Alam Baheramsyah; Ede Mehta Wardhana; Muhammad Azis Husein (International Journal of Marine Engineering Innovation and Research, 2018)
Indonesia's annual marine fish potential of 6.5 million tons is spread over the waters of Indonesia's Exclusive Economic Zone. The constraint of which are often faced by fishermen is the decay that occurs during the storage process in which the fish becomes less fresh when it comes to the fish auction. The decomposition rate of fish after fishing is strongly influenced by fishing techniques, handling techniques, and onboard storage. The cooling or freezing process is the best method chosen for handling the catched fish to maintain its quality and freshness. This study was conducted by modifying the insulation material of purse seine cargo hold using a coolbox made of insulated materials from coconut coir and Palm Fiber. The purpose of this study is to know the influence of coconut coir and Palm Fiber composite insulation to temperature and cooling time in which will be compared with styrofoam insulated coolbox. The study was conducted by testing some specimens which will be selected with the thermal conductivity and lowest density. The compositions which is chosen were coconut coir and Palm Fiber composite that is mixed with polyurethane glue 4:4:1 ratio, having a thermal conductivity of 0.4643 W/mK and a density of 0.18 g/cm3. Coolbox's test using coconut coir and Palm Fiber composite insulation was done using a 400 gram fish as a cooling load and ice that had been destroyed weighing 2 kilograms as a cooling source. Coolbox with coconut coir and Palm Fiber composite insulation has the lowest fish temperature of 0.7oC, while the coolbox with styrofoam insulation has the lowest fish temperature of 1.8oC. In addition, coconut coir and Palm Fiber composite coolbox is able to keep temperature below 20oC for 16,5 hours, while with the same treatment styrofoam insulated coolbox is only able to keep the temperature below 20oC for 16 hours. So it can be concluded the use of coconut coir and Palm Fiber composite is effective as insulation material because it can offset the performance of the insulation styrofoam.